LINGUISTIK TERAPAN DAN KETERAMPILAN BAHASA ARAB (ISTIMA’, KALAM, QIRA’AH, DAN KITABAH) - Umar; Sugondo; Darmadhi, Endhi; Susiawati, Iis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is a library research employing a qualitative-descriptive approach to examine the role of applied linguistics in the development of Arabic language skills, which include listening (istima’), speaking (kalam), reading (qira’ah), and writing (kitabah). Applied linguistics serves as a bridge between linguistic theory and language teaching practice, providing methodological guidance for educators in designing effective and contextual learning strategies. The findings indicate that the integration of applied linguistics contributes to improving phonological awareness, structural accuracy, semantic comprehension, and pragmatic appropriateness in Arabic language learning. Specifically, phonetic and phonological insights enhance listening skills; syntactic and pragmatic understanding support speaking fluency; semantic and discourse analysis strengthen reading comprehension; and cohesion and coherence theory improve writing ability. Thus, applied linguistics plays a fundamental role in promoting both linguistic accuracy and communicative competence in Arabic language education.